Development and validation of a questionnaire to assess the health related Social Capital for Chronic Kidney Disease among Mexican adolescents - Carolina Quiñones-Villalobos; Carlos Alberto Prado-Aguilar; Gregorio Tomás Obrador-Vera; José Manuel Arreola-Guerra; Jannett Padilla-López; Alicia Alanis-Ocádiz; Diana Lorena Cisneros-García; Diana Cristina Navarro-Rodriguez; Laura Leticia Tirado-Gómez (PLoS ONE, 2025)
Background Social Capital on health has been studied widely, to date there is no valid and reliable questionnaire that measure it in Chronic Kidney Disease (CKD). Objective To develop, validate and assess the reliability of Social Capital related to CKD questionnaire for Mexican adolescents. Methods An instrumental study was employed to validate a questionnaire that assesses the cognitive and structural domains of Social Capital related to CKD. The questionnaire was generated by operationalization of the constructs and validated by assessing the content, face validity, criteria and construct validity. Reliability was assessed through the Cronbach´s alpha. Results The content validity of the questionnaire was confirmed through Kendall’s W of 0.925 (p = 0.01) and its face validity was evaluated by four focus groups. A principal component analysis on a sample of 281 adolescents indicated that 72.78% of the variance was explained by the cognitive domain and 83.20% by the structural domain. A confirmatory analysis returned a chi-squared value of 142.99 (p = 0.05), a CFI of 0.97, a TLI of 0.96, a RMSEA of 0.040 and a SRMR of 0.07 for the cognitive domain. Similarly, a chi-squared of 408.296 (p < 0.001), a CFI of 0.98, a TLI of 0.97, a RMSEA 0.03 and a SRMR of 0.06 were returned for the structural domain. The validity of the criteria was assessed through a Pearson’s correlation for both the cognitive and structural domains. There was a mild-to-strongly significant correlation (p ≤ 0.001) among items and dimensions within each domain, with correlation coefficients ranging from 0.23 to 0.83. As a determinant of the reliability of the questionnaire, the Cronbach’s alpha was 0.84 and 0.94 for the cognitive and structural domain, respectively. Conclusions A valid and reliable questionnaire has been developed to measure the influence of Social Capital on health in relation to CKD among Mexican adolescents.